Employee reactions to talent management: Assumptions versus evidence. (13th December 2017) - De Boeck, Giverny; Meyers, Maria Christina; Dries, Nicky
Summary: Two assumptions about employee reactions are currently driving debates around talent management (TM): First, that TM leads to positive outcomes in employees identified as talents; and second, that TM creates differences between talents and employees not identified as talents. This review critically evaluates these assumptions by contrasting theoretical arguments from the non‐empirical literature on employee reactions to TM with the empirical evidence available. Our analysis partly supports both assumptions. Although positive reactions to TM were indeed found in terms of affective, cognitive, and behavioral employee outcomes, our review also found evidence for negative affective reactions in employees identified as talents. Significant differences between talents and non‐talents were found for behavioral reactions, but not for affective and cognitive reactions; for the latter types of reactions, our review found mixed effects. We summarize these findings in an integrative framework on the basis of social exchange theory, which our review shows is the dominant theory underlying assumptions about employee reactions to TM. We propose that 3 elements are missing in our current understanding, which can help explain our review findings: uncertainty, power, and social identity. We conclude with recommendations for TM research and practice.